(3eYQaI GdYdhjGJ hGdchGcH hGdCQVjIs
(3ChdgG (B:s
(3hbO GfJNHfG ef cJGH YJjb dHYV GdYdeGA s
(3BNQgG (B:s
(3QCjJ GdeQA JCcdg GddjGdi cCcd GdCQV SGbWI GdLOjO s
(3GfJNH GdeDda ef cJGH YJjb dHYV GdYdeGA hbO SbWJ efg ChQGb ef Chdg hbO GTJed Ydi eYQaI GdYdhjGJ cGdchGcH hGdCQVjI cGdfHGJ hGdeYGOf hGdLHGd ai BNQ LOGhd ai GdCZPjI hGdCTQHIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI GdchaI (B_ (3HZOGO (B(19) s
Keywords: (3GdadSaI hGdefWbs